Pendekatan Public Relations Politik Bawaslu Buton Selatan dalam Pengawasan Kampanye Pemilihan Umum Tahun 2019 - Rusli Rusli; Fal. Harmonis; Amina Swarnawati (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to find out, explore and describe how the South Buton Bawaslu Political Public Relations approach in the 2019 Election Campaign. Specifically, one of the tasks of the South Buton Bawaslu is to supervise the 2019 election campaign. Here is the role of the South Buton Bawaslu Public Relations Approach. in supervising the 2019 election campaign in South Buton Regency. This research is a qualitative research with in-depth interviews with informants. The results of the study explain that in carrying out the political public relations approach of South Buton Bawaslu there are three approaches, namely the development of a Supervision Community that has been formed in Lawela village, batauga sub-district, Political and Public relations where Bawaslu in this case builds internal coordination in resource development and technical work meetings and in the external public, the Bawaslu of South Buton builds formal communication in the form of discussions and the Grunugian Paradigm where the Bawaslu in this case coordinates in solving common problems and finding joint solutions.